Frequency of Chronic Venous Disease among Nurses - Martanegara, Cendy; Ekowati, RA Retno; Djajakusumah, Teguh Marfen (Althea Medical Journal, 2015)
Â Background: Chronic vein diseases are quite common and its prevalence is also quite high in community. One of the risk factors is occupation with prolonged standing. Quality of life and work efficacy may become risk factors. This disease has not received any special consideration and response.Â Methods: This is a cross-sectional study performed on nurses working in Dr. Hasan Sadikin General Hospital Bandung (n=98; women=76, men=22). The study was conducted in November 2012 through collecting data on prevalence, risk factors, and clinical symptoms by using questionnaire. Chronic venous disease was observed by direct inspection in lower extremities. Diagnosis was concluded according to the Clinical Etiology Anatomy Pathophysiological criteria.Â Results: There was a high frequency, i.e. 86.7% (n=71), of chronic venous disease among nurses, with the age group of 20â29 years old (34.1%) as the age group that was mostly affected. Among female nurses, almost all of them experienced the disease (93.4%; n=71). Clinical symptoms felt by most nurses were heavy feeling on legs (82.3%) and cramps (55.3%).Conclusion: The frequency of chronic venous disease among nurses is high, 86.7% and almost all of the female nurses suffer from the disease. The high frequency in females could be caused by risk factors such as parity and hormonal contraception. Those who are mostly affected by the disease areÂ within range of age 20â29 years old of age. Heavy legs and cramps are the most frequent clinical symptoms felt.Â Keywords: Chronic vein disease, frequency, nursesDOI: 10.15850/amj.v2n1.432Â Â Â